Wilms' tumor with right heart extension: Report of a post-chemotherapeutic fatality - Pradeep Vaideeswar; Jayashri P Chaudhari (Wolters Kluwer Medknow Publications, 2012)
Wilms' tumor (WT) has a strong propensity to invade the vasculature in the form of tumor-thrombus, into the renal veins, and inferior vena cava and even into the right atrium. This cavo-atrial propagation does not alter the prognosis and pre-operative chemotherapy produces shrinkage to the extent of even disappearance of caval or atrial extensions. We present a case of sudden death due to hemorrhagic expansion of the intra-atrial component of WT, immediately after commencement of chemotherapy, an uncommon incident.